2011
DOI: 10.1111/j.1651-2227.2010.02104.x
|View full text |Cite
|
Sign up to set email alerts
|

National guidelines for treatment of jaundice in the newborn

Abstract: Following the introduction of these guidelines, fewer babies in Norway receive phototherapy, and no cases of chronic kernicterus have been reported during this period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
71
0
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 32 publications
2
71
0
13
Order By: Relevance
“…5,9,10 The recent, consensus-based national guidelines published in the UK, South Africa and Norway, include recommendations for the management of preterm infants. 5,11 Recognizing the need, the AAP Committee on Fetus and Newborn in 2007 asked a group of experts to develop a guideline for the management of jaundiced infants <35 weeks of gestation and a recent survey of neonatologist members of the Section on Perinatal Pediatrics of the AAP, 12 confirmed this need. But the current AAP policy requires that guidelines be evidence-based and, as the evidence for such a guideline is limited, it was not possible to comply with this requirement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,9,10 The recent, consensus-based national guidelines published in the UK, South Africa and Norway, include recommendations for the management of preterm infants. 5,11 Recognizing the need, the AAP Committee on Fetus and Newborn in 2007 asked a group of experts to develop a guideline for the management of jaundiced infants <35 weeks of gestation and a recent survey of neonatologist members of the Section on Perinatal Pediatrics of the AAP, 12 confirmed this need. But the current AAP policy requires that guidelines be evidence-based and, as the evidence for such a guideline is limited, it was not possible to comply with this requirement.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] The AAP guideline 1 has been widely adopted in the United States and elsewhere but there is no similar guideline in the United States for the treatment of infants <35 weeks gestation. In lieu of such direction, neonatal intensive care units (NICUs) have established their own criteria for the use of phototherapy and exchange transfusion in these infants, most often based on birth weight or gestational age.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The practical application of phototherapy has earlier been shown to vary greatly, 12 and this still appears to be the case. [13][14][15] Recent data from the Eunice Kennedy Shriver National Institute of Child Health and Human Development Neonatal Research Network comparing 'aggressive' vs 'conservative' phototherapy in extremely low birth weight (ELBW) infants 16 gave us reason to rethink our approach to neonatal jaundice, particularly in the smallest and most immature babies. They found that aggressive phototherapy significantly reduced the rate of neurodevelopmental impairment at 18 to 22 months of age, almost all of which was due to a reduction in profound impairment.…”
mentioning
confidence: 99%
“…The 2004 AAP guidelines for infants born at >35 weeks gestation used graphs but linked those to gestational ages. 19 Others have also chosen graphs 15,20 or used birth weights in lieu of gestational ages. 15 The recommendations are clearly influenced by the results from the Neonatal Research Network, 16,17 and recommend phototherapy at lower levels than others have opted for.…”
mentioning
confidence: 99%
See 1 more Smart Citation